Основні принципи теорії матеріальних артефактів культури - Наконечна, О.В. (Культура народов Причерноморья, 2013)
В даній статі обґрунтовані специфічні особливості теоретичного узагальнення дослідження
матеріальних артефактів культури. Уточнено використання терміну «теорія» в галузі
культурологічного дослідження матеріальних артефактів. Сформульовано вихідний постулат і основні
аксіоматичні положення теорії матеріальних артефактів культури. Зіставлені специфічні особливості
культурологічних теорій та теорій інших наук. Визначена ступінь відповідності теорії матеріальних
артефактів культури основним вимогам до наукового теоретичного узагальнення. В данной статье обоснованы специфические особенности теоретического обобщения
исследования материальных артефактов культуры. Уточнено использование термина «теория» в
области культурологического исследования материальных артефактов. Сформулированы исходный
постулат и основные аксиоматические положения теории материальных артефактов культуры.
Сопоставлены специфические особенности культурологических теорий и теорий других наук.
Определена степень соответствия теории материальных артефактов культуры основным
требованиям к научному теоретическому обобщению. In this article specific features of theoretical synthesis of research artificially created objects of
culture, its material manifestations, that is material artifacts of culture are proved. Term "theory" use in the field
of culturological research of material artifacts is specified.
The initial postulate and the basic axiomatic provisions of the theory of material artifacts of culture are
formulated. The removed axioms are analysed from cultural science positions.
Degree of compliance of the theory of material artifacts of culture to the main requirements to scientific
theoretical generalization is investigated: the type of this theory, form in which it can be expressed, features of
the factual basis of the theory, a way of interpretation of the culturological facts is defined. Features of
observance of requirements of completeness and consistency of the theory of material artifacts of culture are
also specified.
The main restrictions of theoretical research of material artifacts of culture are allocated. The comparative
characteristic of specific features of culturological theories and theories of other sciences is carried out. The
main components of the theory of material artifacts of culture and way of their research are planned.